Gradient approach for the evaluation of the fatigue limit of welded structures under complex loading (Fracture and Structural Integrity, 2017)
Welded ‘T-junctions’ are tested at different load ratio for constant and variable amplitude loading. Fatigue results are analyzed through the type of fatigue mechanisms depending on the loading type. A gradient approach (WSG: Welded Stress Gradient) is used to evaluate the fatigue limit and the comparison with experimental results shows a relative good agreement. Nonlinear cumulative damage theory is used to take into account the variable amplitude loading.
Keywords: Weld; Fatigue; Gradient